Pests of stored beans and their economic importance in Latin America - Schoonhoven, Aart van (International Center for Tropical Agriculture, 1976)
Although bean production in Latin America averaged 3.86 million/yr in 1968-71, literature on bean storage and storage losses in this regions is virtually nonexistent. Among the most important storage pests are Acanthoscelides obtectus and Zabrotes subfaciatus. These 2 especies are similar but differ in oviposition behavior, in that A. obtectus drops the eggs among the seeds, whereas Z subfasciatus attaches them to the seed coat. A. obtectus is a pest in colder areas (higher altitudes or higher latitudes) infesting beans in the field and in storage, while Z. subfasciatus is confined to warmer areas and is a warehouse pest that does not attack beans in undamaged pods. Several minor pests reported in the literature to occur on stored beans may have been found on them accidentally. In a survey of 30 warehouses in Colombia, the av storage period for beans was 44 days. Although bruchids were considered the major storage problem, only 60 percent of the warehouses are fumigated. In 20 percent of the warehouses, beans had been attacked by storage insects. It is hypothesized that due to the high susceptibility of beans to storage pests and the high value of the product, beans are stored for short periods. Under this system few losses from insect attacks occur. (AS)